BIPA Implementasi BIPA (Bahasa Indonesia bagi Penutur Asing) Sebagai Bentuk Soft Diplomacy Indonesia-Thailand 2019-2024 - Juliantini, Novita (Indonesian Journal of Global Discourse, 2023)
ABSTRACT The BIPA program is a form of soft diplomacy because in the process, BIPA not only teaches Indonesian but also introduces Indonesian culture. This is in line with the goal of soft diplomacy, which is to achieve interests in peaceful or non-violent ways, for example by introducing languages and cultures to other countries with the aim of improving their country's positive image and improving bilateral relations. This research aims to find out how BIPA is implemented in Thailand and how BIPA supports Indonesia's soft diplomacy to Thailand in 2019-2024. This study uses the concept of soft diplomacy to see the effectiveness of BIPA in supporting Indonesia-Thailand soft diplomacy. This study uses a qualitative approach with data analysis from interviews, literature studies, and internet-based methods. The results of this study show that BIPA is an important and effective instrument in supporting Indonesia's soft diplomacy to Thailand, because it is able to increase Thai citizens' interest in Indonesian language and culture. This has a positive impact on Indonesia's image and increases its attractiveness as a tourist destination and potential business partner. Keywords: BIPA (Indonesian for Foreign Speakers), Soft Diplomacy, Indonesia, Thailand.